2015
DOI: 10.1016/j.jped.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and allergic diseases in adolescents: nine-year follow-up study (2003-2012)

Abstract: The prevalence of asthma, rhinitis, and atopic eczema in Brazil was variable; higher prevalence values, especially of asthma and eczema, were observed in regions located closer to the Equator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 13 publications
(11 reference statements)
1
22
1
8
Order By: Relevance
“…According to the latest studies, the increase in the prevalence of allergic diseases has plateaued in developed countries, but is still continuing in developing countries [5,6]. However, studies that evaluate the change in the prevalence of allergic diseases in the long term are limited within the literature [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…According to the latest studies, the increase in the prevalence of allergic diseases has plateaued in developed countries, but is still continuing in developing countries [5,6]. However, studies that evaluate the change in the prevalence of allergic diseases in the long term are limited within the literature [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…A study using the ISAAC quiz, the same as that used in this study, evaluated the prevalence of eczema and other allergies in seven Brazilian capitals, where a discordant result was observed, with a median prevalence based on medical diagnosis among 5.6%, in which Belém-Pará presented the highest rate, with 7.9% and Aracaju-Sergipe the lowest, with 3.4% (36). However, in the cohort study developed by Solé et al (36), one can notice a large difference between the self-reported prevalence and the prevalence of medical diagnosis, where the self-reported rate of eczema averaged 9.1%, suggesting the need for new studies with the population studied here to explanation the high rate, since that sampling was for convenience, only for the diagnostic survey of the data presented here and discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda que não exista nenhuma revisão sistemática ou metanálise sobre a epidemiologia da asma no Brasil publicada até o momento, há um bom número de estudos de âmbito nacional publicados nos últimos anos, os quais permitem uma comparação adequada com os dados deste relatório [56][57][58][59][60][61] . Desses, quatro artigos abordam objetivamente a prevalência da asma na população brasileira, sendo três conduzidos com amostras compostas por crianças e adolescentes 56,57,59 e um por indivíduos adultos 61 .…”
Section: Discussionunclassified
“…Desses, quatro artigos abordam objetivamente a prevalência da asma na população brasileira, sendo três conduzidos com amostras compostas por crianças e adolescentes 56,57,59 e um por indivíduos adultos 61 . As principais estimativas nacionais de prevalência de asma entre adolescentes são bastante consistentes entre si 56,57,59 . Em adolescentes de 13-14 anos, a estimativa de prevalência de sintomas de asma varia entre 17,5-23,2%, enquanto a prevalência de asma clinicamente diagnosticada varia entre 12,4-14,3%.…”
Section: Discussionunclassified